Determinação do melhor método para prever o alcance à junção craniovertebral nas cirurgias endoscópicas transnasais utilizando neuronavegação - Aurich, Lucas Alves (2017)
It is expected reduction of surgical complications when craniovertebral junction pathologies are operated using the endoscopic transnasal approach instead of the transoral approach. However, it is yet unclear what is the lower extent of the transnasal approach and which method is better to predict this lower limit in preoperative planning. This study evaluates the inferior exposure of craniocervical junction in 10 patients operated through the transnasal approach using neuronavigation. The intraoperative anatomical limit was compared to nasopalatine and palatine lines. The nasopalatine line predicts more accurately the inferior limit of the transnasal approach.